Marked differences in the effects of levetiracetam and its analogue brivaracetam on microglial, astrocytic, and neuronal density in the rat model of kainic acid-induced temporal lobe epilepsy - Kelemen, Krisztina; Sárosi, Máté; Csüdör, Ágnes; Orbán-Kis, Károly; Kelemen, Hanga; Bába, László; Gáll, Zsolt; Horváth, Eszter; Katona, István; Szilágyi, Tibor (Frontiers in Pharmacology, 2025)
Efficient treatment of temporal lobe epilepsy (TLE) remains challenging due to limited understanding of cellular and network changes and the interference of novel antiepileptic drugs (AEDs) with tissue reorganisation. This study compared the effects of brivaracetam and levetiracetam on histological alterations in key brain regions of the epileptic circuitry, namely, the hippocampus, amygdala, piriform cortex (PC), endopiriform nucleus (EPN) and paraventricular thalamic nucleus (PVT), using the kainic acid (KA) rat model of TLE. Male Wistar rats were assigned to sham-operated (SHAM), epileptic (EPI), brivaracetam- (BRV-EPI) and levetiracetam-treated (LEV-EPI) epileptic groups. Epileptic groups received KA in the right lateral ventricle, which induced status epilepticus followed by a 3-week recovery and latent period. Rats then underwent 3 weeks of oral brivaracetam, levetiracetam or placebo treatment with continuous video monitoring for seizure analysis. Subsequently, triple fluorescent immunolabeling assessed microglial, astrocytic, and neuronal changes. The results showed a drastic increase in microglia density in the EPI and BRV-EPI groups compared to control and LEV-EPI. The BRV-EPI group displayed a significantly higher microglia density than SHAM and EPI groups in the right CA1, CA3 and left CA1 regions, bilateral amygdalae, EPN, PVT and left PC. Astrocyte density was significantly elevated in hippocampal regions of the BRV-EPI group, while neuronal density decreased. Furthermore, brivaracetam did not reduce seizure activity in this disease phase. Significance: Brivaracetam treatment increased microglial activation under epileptic conditions in vivo in all examined brain-regions participating in the epileptic circuitry, in contrast to the effects of levetiracetam, highlighting differences in AED-induced histological alterations.